Quantifying "Peoples' participation and psychological empowerment": A model of individual behaviour in Nepal - Tanner, Philip; Parajuli, Dhirendra B (Occasional Papers in Sociology and Anthropology, 2008)
The PDF of this file is 4,897 kbytes in size and therefore will take a long time to download if you click on the PDF link below. If you would like the file to be sent to you by email, please send a request to info@nepjol.info. Please include the citation below in your request. DOI: 10.3126/opsa.v8i0.1126 Occasional Papers in Sociology and Anthropology Vol.8 2003 p.159-192